Association between osteoporosis and periodontal disease: narrative literature review (Research, Society and Development, 2022)
Introduction: Currently, the interrelationship of systemic conditions with periodontal disease has been studied. One of these conditions is osteoporosis, which results from a disharmony between bone formation and resorption, characterized by a decrease in mineral density and a disorder of skeletal tissue. Periodontal disease is understood as an infectious-inflammatory process that damages the structures of the periodontium when associated with bacterial infection. Periodontal medicine studies the physiological and pathological interaction between the health of the periodontium and the systemic health of the host, based on this principle, it is of great importance to look at the patient as a whole, as systemic repercussions can have consequences in the oral cavity. Objective: To report, through a review of analytical literature, a possible association between periodontal disease and osteoporosis, in order to observe how they occur and make a good diagnosis and treatment for these diseases. Results: Initially, 35 articles were selected, but 26 were used. Recent studies have shown what appears to be a possible relationship between periodontal disease and osteoporosis. Conclusion: There seems to be an association between osteoporosis and periodontal disease, however, more studies need to be carried out since the two diseases share the same risk factors.